2018
DOI: 10.1186/s13020-018-0203-z
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer effects of Rhizoma Curcumae against doxorubicin-resistant breast cancer cells

Abstract: BackgroundChemotherapy is a primary approach in cancer treatment after routine surgery. However, chemo-resistance tends to occur with chemotherapy in clinic, resulting in poor prognosis and recurrence. Nowadays, Chinese medicine may shed light on design of new therapeutic modes to overcome chemo-resistance. Although Rhizoma Curcumae possesses anti-cancer activities in various types of cancers, the effects and underlying mechanisms of its bioactive components against chemo-resistance are not clear. Therefore, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Western blotting assays were conducted according to previous studies [15]. In brief, RAW 264.7 cells were pretreated with SG (0, 25, 50, and 100 μg/mL) for 4 h followed by the addition of LPS (1 μg/mL) for 12 h. The cells were harvested, and the total proteins were extracted with RIPA lysis buffer after the desired drug treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Western blotting assays were conducted according to previous studies [15]. In brief, RAW 264.7 cells were pretreated with SG (0, 25, 50, and 100 μg/mL) for 4 h followed by the addition of LPS (1 μg/mL) for 12 h. The cells were harvested, and the total proteins were extracted with RIPA lysis buffer after the desired drug treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Cancer is a leading public health problem worldwide with an estimated 18.1 million new cases and 9.6 million cancer deaths in 2018 [1]. Chinese herbal medicine has been used as anti-cancer agents for a long time, they exhibit anti-inflammatory activities and contain abundant anticancer compounds that exert direct cytotoxicity effects and indirect regulation in tumor microenvironment and cancer immunity, as well as improve chemotherapy [2][3][4][5]. For examples, PNAS reported that epigallocatechin gallate (EGCG) targeting Laminin receptor (Lam 67R) shows promising efficacy in treating prostate cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…Exponentially growing cells were seeded into 96-well plates at a density of 3,000 cells/well in 100-μl medium and allowed to attach overnight. Cells were treated with designated drugs or drug combinations for 24 h. Cell viability was assessed using MTT method as previously described (Zhong et al, 2018). The concentration for half maximum inhibitory effect (IC 50 ) was calculated by GraphPad Prism 5.…”
Section: Methodsmentioning
confidence: 99%
“…However, although patients are responsive to initial drug treatment, progressive disease occurs invariably, and the response rate becomes decreased due to the occurrence of multidrug resistance (MDR). The main mechanisms of MDR include the increased drug efflux, deregulated apoptosis or survival, alteration of drug targets, as well as adapted metabolic reprogramming (Kesharwani et al, 2018; Zhang et al, 2018; Zhong et al, 2018; Zhou et al, 2019). In most cases, multiple MDR impairments may simultaneously occur, which gives rise to challenge in successful therapies in cancer.…”
Section: Introductionmentioning
confidence: 99%